An introduction to the special issue on X‐ray free‐electron lasers. (1st May 2015) - Schlichting, Ilme; White, William E.; Yabashi, Makina
<x xml:space="preserve">Abstract</x> This issue of the Journal of Synchrotron Radiation is a special issue on X‐ray free‐electron lasers. Here, a brief introduction to these special issue papers is given.